Effect of storage duration on the rheological properties of goose liquid egg products and eggshell membranes - Kumbar, V; Nedomova, S; Trnka, J; Buchar, J; Pytel, R (Poultry science, 2016)
In practice, goose eggs are increasingly used and, therefore, the rheological properties have to be known for processing. The eggs of geese (Landes Goose, Anser anser f. domestica) were stored for one, 2, 3, 4, 6, and 8 wk at a constant temperature 4°C. First of all, the egg quality parameters were described in terms of egg weight, egg weight loss, egg shape index, yolk height, albumen height, yolk index, albumen index, and Haugh units. In the next step the rheological behavior of liquid egg products (egg yolk, albumen, and whole liquid egg) was studied using a concentric cylinder viscometer. Flow curves of all liquid egg products exhibited non-Newtonian shear thinning behavior. This behavior can be described using the Herschel-Bulkley model and for technical application using the Ostwald-de Waele model. The effect of the storage duration on the rheological behavior is different for the different liquid egg products. With the exception of very low shear rates, the viscosity of the egg yolk as well as of the whole liquid egg decreases with storage time. At lower shear rates there is a tendency toward increased albumen viscosity with storage duration. The storage duration also affects the mechanical properties of the eggshell membrane. This effect has been evaluated in terms of the ultimate tensile strength, fracture strain, and fracture toughness. All these parameters increased with the loading rate, but decreased during the egg storage. These mechanical phenomena should be respected, namely in the design of the egg model for the numerical simulation of the egg behavior under different kinds of the mechanical loading.
Keywords: Animals; Egg Shell; eggshell membrane; Geese; skladování potravin; Rheology; Food Storage; husy; egg yolk; ovum; albumen; vaječná skořápka; reologie; viskozita; Ovum; zvířata; Viscosity; liquid whole egg; rheology